Biomimetic Construction of Non‐Iridescent Structural Color Films with High Hydrophobicity and Good Mechanical Stability Induced by Chaotic Convective Coassembly Method. Issue 19 (6th October 2016) - Meng, Yao; Tang, Bingtao; Cui, Junshuo; Wu, Suli; Ju, Benzhi; Zhang, Shufen
Abstract : This article presents an originative strategy to biomimetically construct non‐iridescent structural color films with high hydrophobicity and good mechanical stability. In this strategy, the amorphous array of polystyrene (PS) particles is easily fabricated via a simple chaotic convective flow coassembly method to imitate the amorphous nanostructures of avian feathers. An amorphous array is locked by introducing fluorinated polyacrylate (FPA) latex to the voids between the PS particles as binder, which is similar to the locking effect of an organism of a bird's wing. Meanwhile, the high hydrophobicity (140° contact angle) and good mechanical stability of the films are obtained owing to hydrophobicity of FPA and high roughness of the amorphous array. The as‐prepared films retain their brilliant colors under natural light, and this property is essential for their applications in full‐color displays and responsive materials. Abstract : Non‐iridescent structural color films are biomimetically constructed, and the original method to realizing amorphous array which is like the nanostructure in the bird feature is reported for the first time. Furthermore, high hydrophobic and good stability are obtained which are important in the application of the structural color films.